Etika Konsumsi Pakaian Thrifting dalam Perspektif Maslahah di Kalangan Generasi Z: Antara Hemat dan Konsumtif - Ahmad Fajar Jaelani; Lilik Rahmawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the ethics of thrifting goods consumption in the perspective of maslahah among Generation Z, focusing on the balance between thrift and consumptive goods. The thrifting trend that is rampant among young people is influenced by economic motivation and environmental awareness, but also presents a risk of consumptive behavior due to the influence of social media. This study uses a descriptive qualitative method with semi-structured interview techniques to active students aged 19-24 years who have experience shopping for thrifting goods. The results of the study show that thrifting consumption supports cost savings and environmental sustainability, but can trigger consumptive behavior if not managed wisely. From the perspective of maslahah, thrifting brings benefits (maslahah) when carried out according to the needs and principles of simplicity, but has the potential to cause mafsadah if it only follows trends or prestige. This finding emphasizes the importance of awareness when purchasing thrifiting clothes to be in accordance with the principles of maslahah to create balanced and ethical consumption behavior.